Reinstatement in the Nonunion Sector : An Empirical Analysis - Eden, Genevieve (Relations industrielles / Industrial Relations, 1994)
Reinstatement to the workplace is an important feature of statutory protection against unjust dismissal for nonunion employees. This paper discusses the results of an empirical study of post reinstatement experience of workers under the Canada Labour Code. Overall, the results stand in contrast to the reinstatement experience in union settings which generally show favorable results. The author concludes that the presence of a union may be a key variable in the effectiveness of the reinstatement remedy.